The Gender Reflection - Stephenson, Laura (Auckland University of Technology, 2011)
This thesis investigates how characters with non-traditional gender are depicted in contemporary Western cinema on the basis that this depiction illustrates society’s unease with individuals who do not easily confirm to the standard male-female gender binary. Through focussing on four Western feature films (each of which features non-traditionally gendered character in a leading role), the thesis will argue that, despite the surface appearance of accepting the progressive individual, each film actually reinforces traditional social mobilisations of gender. In order to understand how gender is socially mobilised each film will be closely read with a specific focus on camera, lighting, editing, dialogue, sound, costume and script function. The data will be analysed to assess how characters with non-traditional gender are portrayed on screen and how other characters and social structures respond to them. Although the analysis will reveal concepts of gender progression represented in relatively sophisticated ways, at a deeper level the preferred construction of each of these characters fits within either the male or female gender polarity. Ultimately the thesis will show that within these films the dominant social reaction to people who do not present as either male or female are feared, rejected and ostracised.
Keywords: Gender; Sexuality; Feminism; Body; Androgyny; Transgender; Cinema; Film